An integral and sustainable valorisation strategy of squid pen by-products. (10th November 2018) - Vázquez, José Antonio; Ramos, Patricia; Valcarcel, Jesus; Antelo, Luis T.; Novoa-Carballal, Ramon; Reis, Rui L.; Pérez-Martín, Ricardo I.
Abstract: The aim of this study was to present a sustainable valorisation approach of Loligo opalescens squid pen by-products by optimal production of chitin and chitosan biopolymers and recycling of the generated effluents. The integral recovery of squid pens started with the optimization of the deproteinization process to isolate chitin, including less hazardous enzymatic alternatives to conventional chemical treatments. Response surface methodology analysis yielded optimal conditions of 53.2 °C/pH 8.84 for Alcalase, 54.7 °C/pH 9.16 for Esperase and 0.2 M NaOH/27.5 °C for alkaline hydrolysis. The generated effluents were a good source of organic nitrogen (squid peptones) for the culture of a lactic acid bacterium ( Pediococcus acidilactici ), with biomass and metabolite productions comparable to commercial Man, Rogosa, Sharpe medium. Secondly, optimal process time and alkali concentration for the chemical deacetylation of chitin were established at 16 h/64% NaOH, obtaining high purity chitosan (deacetylation degrees >92%, molecular weights -Mn- ranging from 139 to 300 kDa). Optimized chitin and chitosan processes led to lower energetic costs. Alkaline effluents from chitosan production were applied as a reagent in the selective precipitation of chondroitin sulphate from enzymatic hydrolysates of shark cartilage by-products. Finally, the goodness of the proposed valorisation strategy was evaluated by developing a Material Flow Analysis. Graphical abstract: Image 1 Highlights: Production of chitin and chitosan from Loligo opalescens pens was optimized. Protein effluents from chitin isolation were valorized by microbial bioconversion. Effluents from chitosan isolation were used in chondroitin sulphate production. Sustainability of developed processes was confirmed by Material Flow Analysis.